Overcoming Problems in Learning Arabic Speaking Skills of Class X Students at Madrasah Aliyah Darul Ihsan Samarinda - Said Abdullah; Khairy Abusyairi; Marajo Marajo; Abderazzaq Massouri (El-Syaker : Samarinda International Journal of Language Studies, 2024)
Arabic language learning at Madrasah Aliyah Darul Ihsan Samarinda has been tried as well as possible by the teacher, but there are still many problems in Arabic language learning, especially in speaking skills on the part of students. Therefore, the purpose of this study is to find out what are the problems that occur in learning Arabic, especially in speaking skills and how to solve them. This research is a qualitative research, with the type of descriptive qualitative research. Data collection techniques in the form of observation, interviews, and documentation, data validity is done by triangulating sources and methods, then data analysis techniques using miles and huberman interactive analysis. Based on the results of the research that has been obtained, it shows that the problems in learning speaking skills include: the background of students who are mostly from public schools, the lack of memorization of mufrodat of students, little time to learn Arabic, and the absence of Arabic language environment. While efforts to overcome problems include: teachers provide motivation and enthusiasm in learning Arabic, require memorization of vocabulary so that vocabulary vocabulary is a lot, maximize Arabic learning time, and create a small Arabic language environment.